Life settlements in South Africa: an assessment of the potential for a strong market to develop - Switala, Ryan (My University, 2013)
Life settlement, a transaction whereby the policyholder of a life insurance policy sells the future proceeds of the policy to a third party investor, has established itself as a legitimate alternative asset class in the US over the last decade. This research uses the key supply and demand side forces that fundamentally shaped and continue to underpin the US market, as a framework to assess the possibility of a South African life settlement market developing. Insurance product design, market intermediation, regulation, tax legislation, investment markets, investor rationale and more are explored through in-depth interviews with a range of industry experts. Results suggest that, in principle, there is no definitive reason why a South African life settlement market cannot exist. Across some dimensions the South African primary market may be even more conducive to life settlement transactions than the US. However, in aggregate, these are overshadowed by other forces such as greater investment risk, subtle market nuances and some market size inhibitors that combine to significantly dampen the overall likelihood of the development of a strong market.
MBA thesis
Keywords: Insurance; Life settlements - Insurance